What Role Do Makassar Mall Employee Engagement and Work-Life Balance Play in Determining Job Satisfaction? - Saiful Lizan; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (Universitas KH. Abdul Chalim Mojokerto, 2025)
Using employee engagement as an intermediary variable, this quantitative study examines the effect of work-life balance and work environment on job satisfaction among mall employees in Makassar. The validity, reliability, and causal linkages between variables were examined in this study using the SmartPLS program version 4.0. Employee involvement acted as a mediator between work-life balance, work environment, and job satisfaction, according to the results. employment satisfaction is enhanced when there is a good work-life balance, less work pressure, employment stability, and a pleasant and supportive work environment. While a healthy work-life balance is still important, high employee engagement has a smaller but favourable impact on job satisfaction. If mall management wants their employees to be happy in their jobs, they need to make sure they have a healthy work-life balance, create a positive work atmosphere, and encourage employee engagement. Furthermore, poll results show that employees are still not very satisfied with their jobs because of issues with work-life balance, the workplace, and employee engagement. Employees and a number of internal firm elements are both responsible for the current level of job satisfaction. The role of employee engagement as a moderating variable between work-life balance, work environment, and job satisfaction is further illuminated by this study.